2006
DOI: 10.1007/s10404-006-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-based synthetic method using microflow focusing and droplet fusion

Abstract: Droplet generation and droplet-based microreactor are realized by a facile microfluidic device. The relative concentrations of reactants could be well controlled by adjusting the flow rates without bringing reagents into prior contact; this new method shows considerable advantages for the control and rapid mixing of reagents with no dispersion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 15 publications
1
60
0
1
Order By: Relevance
“…Tanthapanichakoon et al (2006) reported that axial arrangement of droplet constituents enhances mixing and it can be attributed to the reduction of the striation length between reactant segment by interlayering. Similar results for enhanced mixing due to axial arrangement (in-line droplet fusion) have been reported by Liu et al (2007) and Frenz et al (2008). Therefore, it can be stated that axial arrangement of droplet constituents in this merging design leads to enhanced mixing.…”
Section: Enhanced Mixingsupporting
confidence: 85%
“…Tanthapanichakoon et al (2006) reported that axial arrangement of droplet constituents enhances mixing and it can be attributed to the reduction of the striation length between reactant segment by interlayering. Similar results for enhanced mixing due to axial arrangement (in-line droplet fusion) have been reported by Liu et al (2007) and Frenz et al (2008). Therefore, it can be stated that axial arrangement of droplet constituents in this merging design leads to enhanced mixing.…”
Section: Enhanced Mixingsupporting
confidence: 85%
“…To confirm the concentration of blue dye inside the mixed droplet, droplet teams with different VR were provided by adjusting the flow rates of oil and reagents. Then, they were examined by the API method, which were consistent with VR basically (Figure 4c) and the slight deviation is on account of the light curving over the boundary of droplets and software measurement error [25]. …”
Section: Droplet Generation and Fusionmentioning
confidence: 87%
“…The oil phase was introduced into the chip through the two oil inlets, while DI water was injected into inlet A. Then the diluted blue dye was cut into droplets by shear forces from oil phase at the two flow-focusing junctions [25,26]. By precisely controlling the flow rates of continuous phase and dispersed phase, blue dye droplets were arrayed between the DI water droplets in downstream fusing channel.…”
Section: On-chip Operationmentioning
confidence: 99%
“…Besides geometry-based pressure control for droplet mixing [75], merging [76,77] and sorting [78,79], many active control methods have been realized recently, such as hydrostatic pressure [80], temperature gradient [81], thermal expansion [82], optical approaches [83][84][85], magnetic field [86] and electrical control [87][88][89], including electrostactic [90], electrokinetic effect [91], dielectrophoresis [92] and electrowetting [93][94][95][96][97][98]. Among them, electrowetting on dielectric [99][100][101] has been proved to be very effective for cutting, merging, creating and transporting liquid droplets, while its disadvantage is that many electrodes should be fabricated with metallic thin film, causing droplet moving and device fabrication complex, while, with GERF, one can control and manipulate the droplets by much fewer electrodes [102,103].…”
Section: Manipulation Of Dropletsmentioning
confidence: 99%